2019
DOI: 10.1002/fsn3.1035
|View full text |Cite
|
Sign up to set email alerts
|

Effects of power ultrasound on the activity and structure of β‐D‐glucosidase with potentially aroma‐enhancing capability

Abstract: β‐ d ‐glucosidase can release aroma precursors to improve the flavor of plant food, but the hydrolysis efficiency of the enzyme is low; the purpose of this study was to improve the enzyme activity using ultrasound. The effects of ultrasound parameters on β‐ d ‐glucosidase activity were investigated, and the respective structures of enzyme activated and enzyme inhibited were further analyzed. Low temperature (20–45°C), low ultrasonic intensity (<181.53 W/cm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 33 publications
1
34
0
1
Order By: Relevance
“…The main drawback in biocatalytic approach is the hydrolysis time which is too high and therefore requires high loads of enzymes especially in its crude form. Therefore, it is essential to enhance the enzyme activity where ultrasound plays a potential role by reducing the reaction time (Sun et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The main drawback in biocatalytic approach is the hydrolysis time which is too high and therefore requires high loads of enzymes especially in its crude form. Therefore, it is essential to enhance the enzyme activity where ultrasound plays a potential role by reducing the reaction time (Sun et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The reason for the decrease in yield at higher duty cycle was due to extensive cavitation which affect the active conformation of enzyme. On the other side, a lower duty cycle seems to be a better choice for the activation of enzyme [9]. In another study on lipase at different duty cycle showed the maximum enzyme activity at 66.67%.…”
Section: Mechanism Of Intensification Of Enzymatic Reaction Using Ultmentioning
confidence: 97%
“…Ultrasound also changes the secondary structure of enzyme molecules that affects the enzyme activity. A study conducted on β-D-glucosidase showed the increase in α-helices and decrease in β-folds and asymmetrical βfold of β-D-Glucosidase on ultrasound application results in rapid activation of enzyme [9].…”
Section: Mechanism Of Intensification Of Enzymatic Reaction Using Ultmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, an ultrasonication has been approved that can increase enzyme activity at an appropriate frequency and intensity levels because ultrasound can act on conformation changes in enzymes or substrates [ 28 , 29 ]. Ultrasound can improve the activity of many enzymes including α -amylase, β - d -glucosidase, cellulose, dextranase and lipase [ 28 , 30 , 31 , 32 ]. Therefore, this method has been extensively used in various food industries, especially in fruit juice production, where it slightly affects the quality of fruit juice [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%